Statistical energy analysis of structural vibration : numerical, experimental and analytical investigations - Du, Hong Bing. (2008)
This thesis describes work done to study structural vibration in the medium to high frequency range. Attention is focused on Statistical Energy Analysis (SEA), which is the primary high frequency analysis method at present. The principal aim of this thesis is to study the sensitivity of the coupling loss factor (CLF, which is a central parameter in SEA) to variation in the system properties, e.g. damping. An efficient method to measure the CLF is also proposed. The thesis also looks into the method of images. Considering its potential contributions to high frequency vibration analysis in general, and the development of SEA in particular, the theory is extended and the potential for its application is discussed.